Effect of Transcranial Brain Stimulation for the Treatment of Alzheimer Disease: A Review. (25th October 2011) - Nardone, Raffaele; Bergmann, Jürgen; Christova, Monica; Caleri, Francesca; Tezzon, Frediano; Ladurner, Gunther; Trinka, Eugen; Golaszewski, Stefan
Abstract : Available pharmacological treatments for Alzheimer disease (AD) have limited effectiveness, are expensive, and sometimes induce side effects. Therefore, alternative or complementary adjuvant therapeutic strategies have gained increasing attention. The development of novel noninvasive methods of brain stimulation has increased the interest in neuromodulatory techniques as potential therapeutic tool for cognitive rehabilitation in AD. In particular, repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) are noninvasive approaches that induce prolonged functional changes in the cerebral cortex. Several studies have begun to therapeutically use rTMS or tDCS to improve cognitive performances in patients with AD. However, most of them induced short-duration beneficial effects and were not adequately powered to establish evidence for therapeutic efficacy. Therefore, TMS and tDCS approaches, seeking to enhance cognitive function, have to be considered still very preliminary. In future studies, multiple rTMS or tDCS sessions might also interact, and metaplasticity effects could affect the outcome.